MoWhi2 regulates appressorium formation and pathogenicity via the MoTor signalling pathway in Magnaporthe oryzae. (25th May 2021) - Shi, Huanbin; Meng, Shuai; Qiu, Jiehua; Wang, Congcong; Shu, Yazhou; Luo, Chaoxi; Kou, Yanjun
Abstract: Magnaporthe oryzae causes rice blast disease, which seriously threatens the safety of food production. Understanding the mechanism of appressorium formation, which is one of the key steps for successful infection by M . oryzae, is helpful to formulate effective control strategies of rice blast. In this study, we identified MoWhi2, the homolog of Saccharomyces cerevisiae Whi2 (Whisky2), as an important regulator that controls appressorium formation in M. oryzae . When MoWHI2 was disrupted, multiple appressoria were formed by one conidium and pathogenicity was significantly reduced. A putative phosphatase, MoPsr1, was identified to interact with MoWhi2 using a yeast two‐hybridization screening assay. The knockout mutant Δ Mopsr1 displayed similar phenotypes to the Δ Mowhi2 strain. Both the Δ Mowhi2 and Δ Mopsr1 mutants could form appressoria on a hydrophilic surface with cAMP levels increasing in comparison with the wild type (WT). The conidia of Δ Mowhi2 and Δ Mopsr1 formed a single appressorium per conidium, similar to WT, when the target of rapamycin (TOR) inhibitor rapamycin was present. In addition, compared with WT, the expression levels of MoTOR and the MoTor signalling activation marker gene MoRS3 were increased, suggesting that inappropriate activation of the MoTor signalling pathway is one of the important reasons for the defects in appressorium formation in the Δ Mowhi2 and Δ Mopsr1 strains. Our results provide insights into MoWhi2 and MoPsr1‐mediated appressorium development and pathogenicity by regulating cAMP levels and the activation of MoTor signalling in M. oryzae . Abstract : MoWhi2 interacting with MoPsr1 contributes to appressorium development and pathogenicity by regulating intracellular cAMP levels and the activation of MoTor signalling in Magnaporthe oryzae .